Implementation of the Earned Value and Earned Schedule methods for project cost and schedule control in the Icelandic construction industry - Óskar Gísli Sveinsson 1981- (2010)
Ritgerðin er lokuð fram í júlí 2015. The objective of the presented research is to use data gathered from a construction project in Reykjavík from early May 2009 untill March 2010. Cost estimates are created in addition to schedule estimates which are in turn combined into a budget schedule for the earned value analysis. The goal for implementing the earned value and earned schedule methods on an actual construction project is to determine the validity of those methods to the industry. In order to gather the cost and schedule data in a more organized manner a database is created through various scheduling and spreadsheet based systems. The models are used to sort the cost based data aquired from the project and compare the results against the budget schedule in real time. The model also compares the budget schedule against the input for the actual project progress. The project is modelled mostly with a combination of microsoft project and excel spreadsheets to gather the schedule, budget and performance data. In order to make sure that the model represents the dynamic characteristics of the project the schedule is broken down progressively into various tasks and each task is assigned a budget. The model is then reviewed in order to determine if the modelled plan conforms to reality and if the forecasted cost and duration estimates hold true. Úrdráttur á Íslensku: Markmið þessa verkefnis er að nota raungögn sem tekin hafa verið saman frá byggingaframkvæmdum í Reykjavík frá Maí 2009 til Mars 2010. Tilskildar kostnaðar og framkvæmdaáætlanir eru gerðar auk þess sem þær eru sameinaðar með aðferðafræði unnis virðis í tímasetta útgjaldaáætlun. Tilgangurinn þess að innleiða aðferðafræði unnis virðis og unninnar áætlunnar er að ákvarða notagildi þeirra til skipulags innan verktakabransans á Íslandi. Til þess að auka á skilvirkni í gagnaöflun þá er gagnabanki búinn til með hjálp áætlanagerðaforrits og töflureiknis. Líkanið nær í gögn úr gagnabankanum og flokkar þau niður í tilheyrandi tímasetta undirflokka og ber þau ...